Retrospective chart review: Weightbearing CT scans and the measurement of the Lisfranc ligamentous complex. Issue 1 (January 2023) - Falcon, Spencer; McCormack, Thomas; Mackay, Matt; Wolf, Megan; Baker, Jordan; Tarakemeh, Armin; Everist, Brian; Mullen, Scott M.; Schroeppel, John P.; Vopat, Bryan G.
Abstract: Background: Lisfranc Ligamentous Complex (LLC) injuries are commonly misdiagnosed due to their unreliable projection on plain films. Weightbearing CT (WBCT) scans are a relatively new imaging modality that has not yet been utilized to establish widely referenced baseline anatomic positions. Methods: A retrospective chart review was conducted of patients who had undergone weightbearing CT of the bilateral lower extremities with one-hundred and twelve being included (56 patients). Measurements of the Lisfranc joint were collected by two independent reviewers. Uninjured symmetric anatomy was used to describe a baseline for normal anatomic variation and to evaluate for sex-based or age-related differences. These measurements were then compared against the injured side. Results: In patients without Lisfranc injury, the 1st metatarsal base to 2nd metatarsal base distance (Base M1-M2) was 2.7 + /− 0.7 mm; 2nd metatarsal base to medial cuneiform (M2-C1) was 3.7 + /− 0.7 mm; intercuneiform distance was 1.2 + /− 0.3 mm; and sagittal descent 12.2 + /− 5.4 mm. Patients with injury to LLC had a larger M1-M2 base distance (Δ = 0.5903, p < 0.0001) and M2-C1 interval (Δ = 1.8008, p < 0.0001) compared to uninjured side. Males had significantly higher M2-C1 (p = 0.0031), intercuneiform distance (p = 0.0039), and sagittal descent (p = 0.0008) compared to female patients. No significant differences were found between left versus right side in any of the measurements. Intercuneiform distance (p = 0.0039) was found to significantly decrease as age increased, while sagittal descent significantly increased with increased age (p = 0.0066). Conclusion: Weightbearing CT has high utility in identification of Lisfranc injuries particularly when comparing injured and uninjured sides, which may be its greatest utility in defining injuries. This is evident in the excellent diagnostic ability of the M2-C1 measurement. By defining baseline anatomic measurements for Lisfranc complex parameters in our patient population, we provide normal parameters for comparison when evaluating potential subtle injuries. Level of evidence: III